Analisis Bauran Pemasaran Jasa Klinik Rawat Jalan pada RSUD di Propinsi Riau - suroto, bambang (Komunitas Manajemen Kompetitif, 2015)
Abstract: Marketing of hospital services is a challenge in the face of existing problems. At the hospital in Riau Province which is the government health facilities provide services which have the concept of the marketing mix 5 P namely: product, price, place, public relations, and positioning. Hospital marketing mix Riau province in line with the conditions mendepankan some key indicators include: product and services that can be offered outpatient services in hospitals and also services to the home or through an intermediary. Then the price is applied based on a predetermined price and cooperate with BPJS in financing and also with local government programs. Besides the problem location is placed in accordance with public demand for health services and coupled with clinics and health centers that serve the public or before reaching the hospital. Information is provided through socialization and implemented on an ongoing basis through various events and the placement of the existing priority health services in the province of Riau. Keywords: Marketing Mix Hospital Services